Fiscal sustainability using growth-maximising debt targets - Cristina Checherita-Westphal; Andrew Hughes Hallett; Philipp Rother (European Central Bank (ECB), 2012)
This paper highlights the importance of debt-related fiscal rules and derives growth-maximising public debt ratios from a simple theoretical model. On the basis of evidence on the productivity of public capital, we estimate public debt targets that governments should try to maintain if they wish to maximise growth for panels of OECD, EU and euro area countries, respectively. These are not arbitrary numbers, as many of the fiscal rules in the literature suggest, but are founded on long-run optimising behaviour, assuming that governments implement the so-called golden rule over the cycle; that is, they contract debt only to finance public investment. Our estimates suggest that the euro area should target debt levels of around 50% of GDP if member states are to have common targets. That is about 15 percentage points lower than the estimate for the growth-maximising debt ratio in our OECD sample and comfortably within the Stability and Growth Pact's debt ceiling of 60% of GDP. We also indicate how forward looking budget reaction functions fit into a debt targeting framework.
Keywords: H63; E22; O40; 330; Economic Growth; Public capital; public debt